Relative Clause And Its Translation Found In The Story â€œCreatures Behind Housesâ€ - juliarta, I Made (Denpasar Institute, 2021)
This study aims to: (i) analyze the types of relative clauses and its constituent structure found in the novel entitled â€œCreatures Behind Housesâ€, (ii) analyze the types of translation shifts of relative clause in the translation process from source language into target language. This research study focuses on English relative clauses and its translations into Indonesian found in the story entitled â€œCreatures Behind Housesâ€. The research applied the theory of relative clauses which was proposed by Quirk (1985), Sneddon (1996) and the theory of translation shift which was proposed by Catford (1965). The process of collecting data is started by reading the entire data source in order to understand the story and observe the possibility of the data source which could be taken from the story â€œCreatures Behind Housesâ€. The data source was read to find out the types of English relative clauses which were found in the story in the method and technique of collecting the data. The research study found that one type of English relative clauses was found in the story entitled â€œCreatures Behind Housesâ€. It was the type of Restrictive relative clause found in the novel entitled â€œCreatures Behind Housesâ€. Based on the results of analysis, it can be seen that there are four types of English relative clauses found in the data sources with restrictive relative clause as subject and there is 1 type of restrictive relative clause as object found in the â€œCreatures Behind Housesâ€. Secondly, there are two types of translation shifts which were found in the novel. Those are 5 data that were translated in unit shifts and 1 data that was translated by using structure shifts